Heme Oxygenase 1 in Schwann Cells Regulates Peripheral Nerve Degeneration Against Oxidative Stress - Muwoong Kim; Hyosun Kim; Dogyeong Kim; Dokyoung Kim; Youngbuhm Huh; Chan Park; Hyung-Joo Chung; Junyang Jung; Na Young Jeong (ASN Neuro, 2019)
During Wallerian degeneration, Schwann cells lose their characteristic of myelinating axons and shift into the state of developmental promyelinating cells. This recharacterized Schwann cell guides newly regrowing axons to their destination and remyelinates reinnervated axons. This Schwann cell dynamics during Wallerian degeneration is associated with oxidative events. Heme oxygenases (HOs) are involved in the oxidative degradation of heme into biliverdin/bilirubin, ferrous iron, and carbon monoxide. Overproduction of ferrous iron by HOs increases reactive oxygen species, which have deleterious effects on living cells. Thus, the key molecule for understanding the exact mechanism of Wallerian degeneration in the peripheral nervous system is likely related to oxidative stress-mediated HOs in Schwann cells. In this study, we demonstrate that demyelinating Schwann cells during Wallerian degeneration highly express HO1, not HO2, and remyelinating Schwann cells during nerve regeneration decrease HO1 activation to levels similar to those in normal myelinating Schwann cells. In addition, HO1 activation during Wallerian degeneration regulates several critical phenotypes of recharacterized repair Schwann cells, such as demyelination, transdedifferentiation, and proliferation. Thus, these results suggest that oxidative stress in Schwann cells after peripheral nerve injury may be regulated by HO1 activation during Wallerian degeneration and oxidative-stress-related HO1 activation in Schwann cells may be helpful to study deeply molecular mechanism of Wallerian degeneration.